Trion emission from frozen p-n junctions in networks of electrolyte-gated (6,5) single-walled carbon nanotubes - El Yumin, Abdurrahman Ali; Zorn, Nicolas; Berger, Felix J.; Heimfarth, Daniel; Zaumseil, Jana (Carbon, 2023)
We demonstrate exciton and charged exciton (trion) electroluminescence from frozen p-n junctions in networks of polymer-sorted, semiconducting (6,5) single-walled carbon nanotubes. Electrolyte-gating with an ionic liquid was employed to achieve injection and accumulation of high densities of holes and electrons in the nanotube network at low applied voltages. Static p-n junctions were formed by cooling the devices below the melting point of the ionic liquid while in the ambipolar regime. These frozen junctions showed diode-like rectification and enabled the investigation of electron-hole recombination and near-infrared electroluminescence under controlled conditions. The contributions of exciton and red-shifted trion emission to the electroluminescence spectra were influenced by the initial parameters of the p-n junction formation (balanced or unbalanced) and the applied lateral bias, but did not depend on temperature (30-200 K). The tilted potential profile along the fixed junction and consequently the number of excess carriers within the recombination zone were found to predominantly determine the emission intensity and observed trion to exciton ratio.
Online veröffentlicht am 9. November 2022
Gesehen am 07.11.2023